Effects of Response Format on Psychometric Properties and Fairness of a Matrices Test: Multiple Choice vs. Free Response - Breuer, Sonja; Scherndl, Thomas; Ortner, Tuulia M. (Frontiers in Education, 2020)
Reasoning is regarded to be an essential facet of fundamental cognitive abilities. As examinee characteristics may affect performance in Reasoning tests, concern about maintaining fairness is expressed. The purpose of the current study was to examine effects of response format on psychometric properties and fairness of a matrices test according to examinee's sex, risk propensity, and test anxiety. A total of 433 German-speaking pupils (aged 14–20) were randomly assigned to either a multiple choice or a free response version of the same 25-item test. Data analysis yielded Rasch-homogeneous 23-item versions, with higher reliability, but lower criterion validity for the free response test. No interactions between response format and sex, test anxiety, or risk propensity were revealed, but a significant main effect of sex: men out-performed women in reasoning irrespective of response format. Results are discussed with reference to attributes of the test situation and sample characteristics.